Application of response surface methodology for optimization of low calorie burfi incorporated with sucralose and Costus speciosus extract - Anupama, M; M, Dharani kumar; M P, Divya; L, James; SN, Rajakumar (Indian Journal of Dairy Science, 2020)
In this study, Central Composite Rotatory Design (CCRD) of Response Surface Methodology (RSM) was used for the optimization of levels of Costus speciosus extract and sucralose in the low calorie burfi. The response variables used were sensory characteristics: flavour, body and texture, colour and appearance, sweetness and overall acceptability. Coefficient of determination (R2) ranged from 81 per cent to 92 per cent for all the attributes and the Adequate Precision Value (APV) came in the range of 5.87 to 10.09. From the models, the optimum level of Costus speciosus extract and sucralose to achieve the predicted maximum response values were found to be 63.12 and 151.85 ppm respectively.Â The developed product was analysed for its physico-chemical properties and microbiological characteristics. The product was found to contain 26.98 percent fat, 25.43 per cent protein, 18.58 per cent lactose, 81.40 per cent total solids, 4.6 percent ash, 18.60 percent moisture and 0.36 per cent lactic acid. Freshly prepared low calorie burfi had a Standard Plate Count (SPC) of 4.82 log10cfu/g and yeast and mould count of 1.90 log10cfu/g. Coliform count was found to be absent in the samples.